Nonylphenol exposure in 7-year-old Japanese children between 2012 and 2017– Estimation of daily intakes based on novel urinary metabolites. (March 2022) - Ringbeck, Benedikt; Bury, Daniel; Ikeda-Araki, Atsuko; Ait Bamai, Yu; Ketema, Rahel Mesfin; Miyashita, Chihiro; Brüning, Thomas; Kishi, Reiko; Koch, Holger M.
Graphical abstract: Highlights: Ubiquitous nonylphenol (NP) exposure in 7-year-old Japanese children (n = 180). Specific urinary biomarkers OH-NP and oxo-NP detected in 100% and 66% of samples. Median and maximum daily NP intakes at 0.14 and 0.95 µg/(kg bw*d). Associations of OH-NP and oxidative stress biomarkers HEL and HNE. Only slight annual decrease in NP exposure of 4.7% between 2012 and 2017. Abstract: Nonylphenol (NP) has been under scrutiny for decades due to its endocrine-disrupting properties and its ubiquity in the environment. Despite its widespread occurrence, robust and reliable exposure data are rare. In this study, we used human biomonitoring (HBM) measuring the novel urinary alkyl-chain-oxidized biomarkers OH-NP and oxo-NP to determine NP exposure in 7-year-old Japanese children. The new biomarkers are advantageous over measuring unchanged NP because they are not prone to external contamination. We analyzed 180 first morning void urine samples collected between 2012 and 2017. OH-NP and oxo-NP were detected in 100% and 66% of samples at median concentrations of 2.69 and 0.36 µg/L, respectively. 10-fold concentration differences between OH-NP and oxo-NP are in line with recent findings on human NP metabolism. Based on OH-NP we back-calculated median and maximum NP daily intakes (DI) of 0.14 and 0.95 µg/(kg bw*d). These DIs are rather close to but still below the current provisional tolerable daily intake of 5 µg/(kg bw*d) by the Danish Environmental Protection Agency. Between 2012 and 2017 the DIs decreased by an average of 4.7% per year. We observed no seasonal changes or gender differences and questionnaire data on food consumption, housing characteristics or pesticide use showed no clear associations with NP exposure. Urinary OH-NP was weakly associated with the oxidative stress (lipid peroxidation) biomarkers N -ε-hexanoyl-lysine (HEL) and trans -4-hydroxy-2-nonenal (HNE) (Spearman ρ = 0.30 and 0.22, respectively), but not with 8-hydroxy-2′-deoxyguanosine (8-OHdG). Further research is needed to identify and understand the major sources of NP exposure and to investigate a potential role in oxidative stress. This study is the first to investigate NP exposure in Japanese children based on robust and sensitive HBM data. It is a first step to fill the long-standing gap in quantitative human NP exposure monitoring and risk assessment.